2015
DOI: 10.1111/bij.12587
|View full text |Cite
|
Sign up to set email alerts
|

Morphological variation between populations of the expanding ectoparasitic deer kedLipoptena cervi(Diptera: Hippoboscidae) in Fennoscandia

Abstract: We examined morphological and genetic differences among Fennoscandian deer ked (Lipoptena cervi L, Hippoboscidae) populations with varying expansion history: the eastern population (Finland) has expanded rapidly, whereas the western population is divided into an old and relatively stationary sub-population in Sweden and a newly established and more expansive sub-population in Norway. The genetic analysis suggests that the distinct populations represent a single species. Individuals from expansive populations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 69 publications
0
8
0
1
Order By: Relevance
“…Lipoptena cervi was the only deer ked species microscopically and molecularly identified on C. capreolus , C. elaphus , R. rupicapra and O. aries musimon in the present study. Despite the expected presence of slight morphological variations (Jakoola et al ., ), no misidentification occurred with any other Lipoptena spp., as confirmed by PCR amplification and analysis of CO1 and CAD gene fragments.…”
Section: Discussionmentioning
confidence: 77%
“…Lipoptena cervi was the only deer ked species microscopically and molecularly identified on C. capreolus , C. elaphus , R. rupicapra and O. aries musimon in the present study. Despite the expected presence of slight morphological variations (Jakoola et al ., ), no misidentification occurred with any other Lipoptena spp., as confirmed by PCR amplification and analysis of CO1 and CAD gene fragments.…”
Section: Discussionmentioning
confidence: 77%
“…Thus, molecular analysis could help determine the species of deer keds correctly. Jaakola et al (2015) have demonstrated that in Scandinavian countries (Norway, Sweden, and Finland), the genetic diversity among L. cervi is very low; the genetic diversity between and within different populations is only 0.1%. Kurina et al (2019) showed that intra-specific genetic distances in L. cervi vary from 0.000 to 0.026 (average 0.002 ± 0.004 SD) and in L. fortisetosa from 0.000 to 0.023 (0.01 ± 0.007 SD average).…”
Section: Discussionmentioning
confidence: 99%
“…Dalsze badania porównawcze (24) potwierdziły obserwowane różnice. Tymczasem wyniki badań molekularnych prowadzonych w Skandynawii wskazują na istnienie kilku populacji w obrębie jednego gatunku Lipoptena cervi, pasożytującego u jeleniowatych, których duża zmienność morfologiczna wynika głównie z wpływu czynników klimatycznych (20).…”
Section: Biologia I Opis Gatunków Pasożytówunclassified